2002
DOI: 10.1002/neu.10153
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of subunit composition in nAChRs: Evolutionary origins, physiologic and pharmacologic consequences

Abstract: Nicotinic acetylcholine receptors are made up of homologous subunits, which are encoded by a large multigene family. The wide number of receptor oligomers generated display variable pharmacological properties. One of the main questions underlying research in molecular pharmacology resides in the actual role of this diversity. It is generally assumed that the observed differences between the pharmacology of homologous receptors, for instance, the EC 50 for the endogenous agonist, or the kinetics of desensitizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
264
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(271 citation statements)
references
References 80 publications
5
264
0
2
Order By: Relevance
“…Data acquisition was conducted through the Clampex 9.2 program (Axon Instruments). Dose-response curves were generated from macroscopic peak currents (I) obtained from 7 different ACh concentrations (1,3,10,30,55,100, and 300 M ACh). Dose-response curves were fitted through the sigmoidal dose-response equation with variable slope using the GraphPad Prism 4 program (GraphPad),…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data acquisition was conducted through the Clampex 9.2 program (Axon Instruments). Dose-response curves were generated from macroscopic peak currents (I) obtained from 7 different ACh concentrations (1,3,10,30,55,100, and 300 M ACh). Dose-response curves were fitted through the sigmoidal dose-response equation with variable slope using the GraphPad Prism 4 program (GraphPad),…”
Section: Methodsmentioning
confidence: 99%
“…The acetylcholine receptor (AChR) 2 belongs to the superfamily of the ligand-gated ion channel receptors that are of fundamental importance in the chemical synaptic transmission throughout the nervous system (1)(2)(3)(4). Defects in the AChR function could affect the transmission of nerve signals across synapses and cause pathological diseases such as the congenital myasthenic syndromes (5).…”
mentioning
confidence: 99%
“…Although most nAChR subunits assemble only into heteromeric nAChRs (9,10), the ␣7 and ␣8 subunits are important exceptions. Both ␣7 and ␣8 are able to generate functional homomeric nAChRs (11,12) and have much closer sequence similarity to each other than to other nAChR subunits (2,9).…”
mentioning
confidence: 99%
“…Previous studies have indicated that the nicotinic binding site is located at the centre of the extracellular domain of the receptor and lies at the interface between  and β subunits, which are known as the principal (P) and complementary (C) components, respectively [48][49][50]. Several residue stretches referred to as loops A, B and C in the  subunit, and D, E and F in the β subunit shape the binding site (in the following the symbols "" and "β" will be used before the residue to indicate the subunit it belongs to, and the numbering refers to the 4 and β2 subunits in rat).…”
Section: Binding Mode Of Mdmamentioning
confidence: 99%
“…To address the binding of MDMA to the 42 receptor, the homology model of the extracellular domains of the neuronal rat (4) 2 (2) 3 nAChR subtype constructed by Le Novère et al was used (PDB ID: 1OLE) [49]. The 3D model was refined with the software MOE 2008.10.…”
Section: Molecular Modeling Studies: System Setup and Dockingmentioning
confidence: 99%